A genome‐wide association study of coping behaviors suggests FBXO45 is associated with emotional expression. (11th May 2018) - Shimanoe, C.; Hachiya, T.; Hara, M.; Nishida, Y.; Tanaka, K.; Sutoh, Y.; Shimizu, A.; Hishida, A.; Kawai, S.; Okada, R.; Tamura, T.; Matsuo, K.; et al.
Abstract : Individuals use coping behaviors to deal with unpleasant daily events. Such behaviors can moderate or mediate the pathway between psychosocial stress and health‐related outcomes. However, few studies have examined the associations between coping behaviors and genetic variants. We conducted a genome‐wide association study (GWAS) on coping behaviors in 14088 participants aged 35 to 69 years as part of the Japan Multi‐Institutional Collaborative Cohort Study. Five coping behaviors (emotional expression, emotional support seeking, positive reappraisal, problem solving and disengagement) were measured and analyzed. A GWAS analysis was performed using a mixed linear model adjusted for study area, age and sex. Variants with suggestive significance in the discovery phase ( N = 6403) were further examined in the replication phase ( N = 7685). We then combined variant‐level association evidence into gene‐level evidence using a gene‐based analysis. The results showed a significant genetic contribution to emotional expression and disengagement, with an estimation that the 19.5% and 6.6% variance in the liability‐scale was explained by common variants. In the discovery phase, 12 variants met suggestive significance ( P < 1 × 10 −6 ) for association with the coping behaviors and perceived stress. However, none of these associations were confirmed in the replication stage. In gene‐based analysis, FBXO45, a gene with regulatory roles in synapse maturation, was significantly associated with emotional expression after multiple corrections ( P < 3.1 × 10 −6 ). In conclusion, our results showed the existence of up to 20% genetic contribution to coping behaviors. Moreover, our gene‐based analysis using GWAS data suggests that genetic variations in FBXO45 are associated with emotional expression. Abstract : A significant association was identified between a gene encoding F‐Box Protein 45 and emotional expression as human coping behavior.